2013
DOI: 10.9767/bcrec.8.1.4394.14-33
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Heterogeneous Acid-Base Catalysts for Fragrances Synthesis: A Review

Abstract: This paper reviews various types of heterogeneous acid-base catalysts for fragrances preparation. Catalytic activities of various types of heterogeneous acid and base catalysts in fragrances preparation, i.e. non-zeolitic, zeolitic, and mesoporous molecular sieves have been reported. Generally, heterogeneous acid catalysts are commonly used in fragrance synthesis as compared to heterogeneous base catalysts. Heteropoly acids and hydrotalcites type catalysts are widely used as heterogeneous acid and base catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Characterisation and catalytic activity examination of modified synthetic zeolites and natural zeolites from several countries were reported on some organic reactions such as in Knoevenagel condensation reaction [6], synthesis of fragrances [7], and cyclisation of citronellal into isopulegol [8,9]. Cyclysation-acetylation of citronellal with FeCl3 Catalyzed showed that in high temperature selectivity to produce IPA was low, and the major product was p-cymene as the side product [10].…”
Section: Introductionmentioning
confidence: 99%
“…Characterisation and catalytic activity examination of modified synthetic zeolites and natural zeolites from several countries were reported on some organic reactions such as in Knoevenagel condensation reaction [6], synthesis of fragrances [7], and cyclisation of citronellal into isopulegol [8,9]. Cyclysation-acetylation of citronellal with FeCl3 Catalyzed showed that in high temperature selectivity to produce IPA was low, and the major product was p-cymene as the side product [10].…”
Section: Introductionmentioning
confidence: 99%